Police subculture and the influence of machismo on women’s position in the police - Subošić, Dane R; Vranešević, Milena (Sociološki pregled, 2021)
The aim of this research was to establish the position of women in the police force regarding the fact that this profession is traditionally considered to be a male working environment, in which it is easy to discern the presence of “machismo”. With that in mind, it was necessary to explore the attitudes, values and convictions among the members of the police force, who are a part of the police subculture. For that purpose 90 police officers – male and female, were interviewed in the Police Department in Sremska Mitrovica. The results of the empirical research show that there is an improvement in the field of integration of women in the police force. However, there are still significant differences between male and female respondents when it comes to the comprehension of the competence of women for the police work.